Precursor sticking coefficient determination from indented deposits fabricated by electron beam induced deposition - Kuprava, Alexander; Huth, Michael (Beilstein Journal of Nanotechnology, 2025)
A fast simulation approach for focused electron beam induced deposition (FEBID) numerically solves the diffusion–reaction equation (continuum model) of the precursor surface on the growing nanostructure in conjunction with a Monte Carlo simulation for electron transport in the growing deposit. An important requirement in this regard is to have access to a methodology that can be used to systematically determine the values for the set of precursor parameters needed for this model. In this work we introduce such a method to derive the precursor sticking coefficient as one member of the precursor parameter set. The method is based on the analysis of the different growth regimes in FEBID, in particular the diffusion-enhanced growth regime in the center region of an intentionally defocused electron beam. We employ the method to determine the precursor sticking coefficient for bis(benzene)chromium, Cr(C6H6)2, and trimethyl(methylcyclopentadienyl)platinum(IV), Me3CpPtMe, and find a value of about 10−2 for both precursors, which is substantially smaller than the sticking coefficients previously assumed for Me3CpPtMe (1.0). Furthermore, depositions performed at different substrate temperatures indicate a temperature dependence of the sticking coefficient.
Keywords: adsorption; continuum model; FEBID; nanofabrication; sticking coefficient